Improving the material efficiency of furnishes in papermaking by stratification and chemical modifications - Oksanen, Antti (2012)
In this thesis the surface chemistry of fibres and z-directional paper structure were modified in order to improve the material efficiency of the fibres in the papermaking process. Material efficiency was estimated by measuring dewatering characteristics, wet web strength properties and end product quality from pulp and paper specimens. Chemical and mechanical pulps were modified by removing specific carbohydrates from the fibre and fines surface or alternatively polysaccharides were added to the fibre surface. Enzymes were utilised for the partial hydrolysis of cellulose and hemicelluloses from the fibre, whereas polysaccharides such as uncharged xyloglucan and cationic starch were added to pulp suspension or sprayed into wet paper sheets. The benefit of using uncharged chemicals is that they do not interfere with process waters like charged additives. Paper sheets of layered furnish structures were prepared with a multilayer sheet former. The effect of stratification of filler and chemical and mechanical pulps on papermaking and paper properties were evaluated. Additionally, two novel methods for analysis of z-directional furnish distribution in the paper were developed. According to the results, dewatering characteristics of mechanical and chemical pulps in forming, wet pressing and drying sections can be enhanced by the use of hydrolytic enzymes. However, the role of different wood carbohydrates differs depending on the pulp type and structure of the dewatering section. Modification of merely the cellulose part of fibre seems to enhance dewatering in the forming section and in the drying section with both mechanical and chemical pulps. In general, nearly 1% hydrolysis of wood carbohydrates of TMP (thermomechanical pulp) was found to be necessary to enhance the dewatering in the forming section. In the case of TMP, it was also found that the combined partial hydrolysis/removal of cellulose and galactoglucomannan enables higher wet pressing pressure and thus dewatering without loss of bulk of the paper. The introduction of xyloglucan-based chemicals and cationic starch into paper had positive influences on the dry strength properties of paper, as expected. Interestingly, xyloglucan-based treatments also increased the initial wet strength and drying forces of the paper samples, contrary to the effect of cationic starch. The cross-linking of xyloglucan with borate and the introduction of aldehyde groups to xyloglucan were found to further enhance both wet and dry paper strength properties. Aldehyde-xyloglucan was noted as being the most effective of the applied chemicals. The formation of covalent hemiacetal bonds due to aldehyde groups in the wet fibre network (before hydrogen bonds are created) was expected to have an important role in the strengthening of wet paper samples after wet pressing. Xyloglucan and xyloglucan-borate complex were also found to improve the bonding ability of the dried and re-pulped fibre. The xyloglucan-based treatment of the fibre surface could thus increase the strength of paper made of recovered fibres. Contrary to cationic starch, xyloglucan was found to recover the strength properties decreased by treatments with hydrolytic enzymes. The uncharged nature, the high affinity to cellulose and the similarity of the XG backbone and cellulose chain may explain the results. Thus, the enzymatic treatment of pulp followed by xyloglucan modification of the fibre network offers an interesting possibility to enhance dewatering characteristics at the same time without any deterioration of dry strength properties. Water adsorbing polysaccharides forming a gel layer on the surface of the fibre were concluded to play an important role in the material efficiency of the fibre. The reduction of softwood pulp content in fine paper combined with the stratification of TMP in the middle layer and hardwood pulp in the surface layer, enhanced wet web strength and dry sheet smoothness at the same time. The stratification of fillers into surface layers contributed to enhanced tensile strength compared to an even addition of filler to all layers. The result is probably due to the non-linear relationship between filler content and tensile strength. Additionally, it was noted that the utilisation of 10 to 20% of TMP enabled a 10% addition of filler without any deterioration in the wet web tension holding ability. The results of this thesis demonstrate that the material efficiency of the fibre can be improved by utilising several unconventional methods. The modification of fibre surface chemistry and fibre network structure in the thickness direction of the paper can substantially improve production efficiency and improve end product quality. The results of this thesis can be utilised for example in enhancing the recyclability of pulp fibres, reducing the basis weight of paper and board or in utilising coarse (low energy) pulp in papermaking.